PREVALENCE OF DEATHS CAUSED BY ZINC PHOSPHIDE POISONING IN FORENSIC CASES - Mohammad Sadeq Ahmadi; Hassibulla Baha Nijrabi; Mohammad Taqi Anwari; Ehsanullah Alemi (Interdisciplinary Approaches to Medicine, 2024)
Background: Zinc phosphide is a dark grey or black substance commonly used as a rodenticide in developing countries to protect grains and legumes. When ingested, it reacts with stomach acid to release phosphine gas, which can be absorbed through the gastrointestinal tract and lungs, leading to zinc phosphide poisoning. The results of this research will help the police and other security agencies to consider and implement the necessary measures to reduce poisonings and deaths caused by zinc phosphide, which is used for suicide, murder, and accidents.